ANALISIS MULTI RESOURCE ALLOCATION PADA PROYEK IT (STUDI KASUS : PROYEK PEMBUATAN SISTEM INFORMASI ERP) - Dinda Tria Pratiwi, (2021)
ERP information system development project for PT. XY is a project undertaken by PT. J by adjusting the desired and required customizations from PT. XY. Constraints in the initial plan of this project, namely requiring more time and overtime to meet the limited human resources in the project. Thus, it requires the right method and must be reconsidered carefully for the final planning. The Multi Resource Allocation method is used for equitable distribution of human resources in the project so that the fulfillment of human resource needs is optimal. This method is also assisted by the use of options available to Ms. Project, namely resource leveling with slack, without slack, and with splits. The result is that among the three methods, the best solution is obtained, namely resource leveling with splits that have no overallocation and a faster time duration with 336 working days and a cost of Rp. 621,305,000.